Statistical analysis of the prevalence, severity and some possible etiologic factors of gingival recessions among the adult population of Thamar city, Yemen - Abdullah Gh. Amran; Mansour Ali S. Ataa (Revista Sul-Brasileira de Odontologia, 2012)
Introduction and objectives: Gingival recession is an undesirable condition resulting in root exposure which is often not esthetic and may lead to sensitivity and root caries. The objective of the current study was to quantify and analyze the prevalence and severity of the gingival recession problem and also to identify the influence of some risk factors on gingival recession’s occurrence. The current study is arguably important because there was no previous study of this type in Yemen. Material and methods: This study was performed on 602 non missing teeth participants of age class ≥ 20 years old who attending the learning dental clinics of faculty of dentistry at Thamar University, and Thamar General Hospital during the period January to October 2010. All measurements of gingival recession and loss of attachment were done with periodontal probe and under sufficient illumination. Furthermore the severity of gingival recessions was evaluated based on Miller’s classification. Some measurements were done twice randomly in order to examine intraobserver agreement of data. Statistical analysis was accomplished using Chi-squares test and Logistic Linear Regression. Results: Our findings showed that 60.5% of patients had gingival recessions. The trend of gingival recession was upward within 20-29 (15.0%) to 30- 39 years of age (16.8%) and was descending within 40-49 (15.9%) to 50 years of age and older (12.8%). Prevalence of gingival recession in females (33.6%) was found to be significantly higher than that in males (26.9%), (P<0.05). The localized recession (26.7%) and that of generalized (33.7%) were found to be significantly different, (P<0.05). The most significant differences of prevailed recessions were detected in buccal-labial & balatal-lingual (44.5%) and the upper & lower teeth (34.6%), respectively, (P<0.05). In addition, the recession in the anterior teeth (25.7%) was significantly much higher than that in posterior teeth (6%). Moreover, Class I Miller was significantly (P<0.05) the most common type of recession (30.5%) when compared to the other classes. The recession percentages of gingival recession size; < 3 mm (26.9), 3-4 mm (9.1) and > 4 mm (24.4), were found to differ significantly, (P<0.05). Similarly, the percentages of recessions in loss of attachment size; < 3 mm (8.8), 3-4 mm (9.3) and > 4 mm (42.5), were also significantly different, (P<0.05). Finally, the relationship between gingival recession and the concomitant risk factors was significant (P<0.05). Conclusion: Considering the high prevalence of gingival recession (60.5%) among Yemeni population may relate to the destructive periodontitis, and khat chewing so the implementation of oral hygiene instructions programs among Yemeni population would be a necessity.